Solve for y -(y+5)-4=-2(y-6)

Math
-(y+5)-4=-2(y-6)
Simplify -(y+5)-4.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-y-1⋅5-4=-2(y-6)
Multiply -1 by 5.
-y-5-4=-2(y-6)
-y-5-4=-2(y-6)
Subtract 4 from -5.
-y-9=-2(y-6)
-y-9=-2(y-6)
Simplify -2(y-6).
Tap for more steps…
Apply the distributive property.
-y-9=-2y-2⋅-6
Multiply -2 by -6.
-y-9=-2y+12
-y-9=-2y+12
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 2y to both sides of the equation.
-y-9+2y=12
Add -y and 2y.
y-9=12
y-9=12
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 9 to both sides of the equation.
y=12+9
Add 12 and 9.
y=21
y=21
Solve for y -(y+5)-4=-2(y-6)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top